Interest rates, cash and short-term investments - Ysmailov, Bektemir (Journal of Banking & Finance, 2021)
This paper addresses the recent mixed evidence on the relationship between interest rates and corporate liquidity. I find that high (low) interest rates are associated with high (low) short-term investments and low (high) cash due to the opportunity cost of holding the latter. Further, I show that interest rates are negatively related to total liquid assets, i.e., the sum of cash and short-term investments. These patterns suggest a two-level demand for liquidity. At the top level, there is demand for overall liquidity and an increase in interest rates increases its price resulting in a negative effect. At the bottom level, once the firm has decided its overall level of liquidity, it chooses what fraction to hold in cash versus short-term investments. An increase in interest rates increases the price of cash relative to short-term investments resulting in a decrease in the former and an increase in the latter.